A Deterministic Framework for Incremental System Isolation: Securing Financial Integrity and Public Safety in Distributed Platform Architectures - Sowjanya Puligadda (Malikussaleh University, Aceh, Indonesia, 2026)
As digital platforms continue to expand in scale, complexity, and regulatory oversight, maintaining strict separation between experimental development environments and live production systems has become both a technical requirement and a governance imperative. In highly regulated sectors, including financial services, transportation, healthcare, and critical national infrastructure, inadequate isolation between non-production and production environments can lead to regulatory violations, financial losses, security breaches, and service disruptions affecting end users. This paper proposes the Multi-Tiered Incremental Isolation Framework (MTIIF), a deterministic architectural model designed to establish verifiable physical and logical segregation between development, testing, staging, and production environments. The framework integrates three complementary architectural mechanisms: cryptographic tenancy propagation embedded within distributed tracing headers to ensure end-to-end environment identity, physical segregation of storage and event-stream infrastructures for high-risk services, and autonomous regulatory guardrails implemented through CI/CD-integrated linting, policy validation, and deployment verification tools. Unlike conventional isolation strategies that rely primarily on operational procedures, the proposed incremental adoption model enables organizations to prioritize protection of high-risk service domains while progressively extending isolation across the entire service mesh with minimal operational disruption. Evidence from industrial deployments demonstrates that the framework reduces testing-related production incidents to statistically negligible levels, eliminates cross-environment data contamination responsible for financial integrity failures, and provides cryptographically verifiable audit trails supporting compliance with international regulatory standards. Furthermore, the framework improves operational resilience, deployment confidence, and software governance by transforming environmental isolation into a mathematically enforceable architectural invariant rather than a procedural practice dependent on human discipline. These findings establish MTIIF as a scalable reference architecture for secure, compliant, and resilient cloud-native enterprise platforms supporting continuous software delivery